1989
DOI: 10.1099/0022-1317-70-8-2075
|View full text |Cite
|
Sign up to set email alerts
|

The Anterograde Transport of Rabies Virus in Rat Sensory Dorsal Root Ganglia Neurons

Abstract: SUMMARYWe have previously described the capacity of neurites extending from cultured rat sensory dorsal root ganglia (DRG) neurons to transport rabies virus through axoplasm in the retrograde direction. Here we report the infection of cultured neurons derived from the DRG and the subsequent anterograde transport of rabies virus from the infected cell somas through the extending neurites to its release into the culture supernatant. Viral transport was monitored by titration of the virus yield in the external co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 47 publications
(36 reference statements)
1
34
0
1
Order By: Relevance
“…Previous tracing studies using rabies virus consistently demonstrated that peripheral uptake of rabies virus typically occurs at motor terminals and propagates retrogradely via exclusive trans-synaptic transfer into presynaptic neurons (23,33,55). However, in animal species such as mice, which have a particular affinity for fixed rabies strains (due to their passage history), the virus can enter into peripheral terminals of sensory neurons and move in an anterograde manner (24)(25)(26). The question is whether the spread of rabies to other neurons from infected primary sensory neurons happens primarily with presynaptic partners or nonselectively to any nearby neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous tracing studies using rabies virus consistently demonstrated that peripheral uptake of rabies virus typically occurs at motor terminals and propagates retrogradely via exclusive trans-synaptic transfer into presynaptic neurons (23,33,55). However, in animal species such as mice, which have a particular affinity for fixed rabies strains (due to their passage history), the virus can enter into peripheral terminals of sensory neurons and move in an anterograde manner (24)(25)(26). The question is whether the spread of rabies to other neurons from infected primary sensory neurons happens primarily with presynaptic partners or nonselectively to any nearby neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, through intraganglion spreading of the replicated viruses, more DRG neurons were labeled in Avil-Cre RΦGT mice (~3,600) than in Trpv1-Cre RΦGT mice (~2,300). the commonly used "fixed" strains of rabies virus could infect mouse primary sensory neurons from axon terminals, could be transported anterogradely in these neurons, and could be released from their axon terminals (24)(25)(26). We have previously developed a mouse line that enables Cre-dependent complementation of the deficient rabies virus (RΦGT mouse) (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Ocasionalmente, el virus puede llegar directamente al sistema nervioso central sin replicarse en los músculos (6). Las partículas virales ingresan a las células nerviosas por endocitosis, en la terminal sináptica de la placa neuromuscular, y viajan a través de los tractos nerviosos por medio del transporte axonal retrógrado (2,5); así logran invadir la médula espinal y posteriormente el encéfalo (7).…”
unclassified
“…Yet, the molecular basis for the transport of the RV particle remains unclear and controversial. Most transneuronal studies of the CNS in nonhuman primates (5,6) and mice (7,8) reveal that fixed (laboratory-adapted) strains of RV spread exclusively in the retrograde direction; however, past in vitro and in vivo studies suggest that anterograde transport might also be involved (7,(9)(10)(11). The discovery that the dynein light chain, LC8 (DNLC1), interacts with the RV phosphoprotein (RVP) provides a putative molecular link between the virus and host cell transport system and, thus, a potential mechanism for the neuroinvasive property of RV.…”
mentioning
confidence: 99%